Preparing schools and teachers for teaching English to young learners - Samuel Lefever (2008)
Fyrirlestur haldinn á „Den 10. nordiske læreruddannelseskongres” sem haldin var í Kennaraháskóla Íslands 21.-24. maí 2008 In recent years there has been a growing interest in offering English instruction to children at ever younger ages. In many countries in Europe English is taught from the beginning grades in schools. This trend has also taken hold in Iceland and an increasing number of schools and even some preschools are beginning to offer English at early ages. This paper discusses the findings of two recent surveys of English language teachers in Icelandic primary schools (grades 5-7) carried out in spring 2007. The objectives of the studies were to gather information about English teaching at the beginning level.